PENGARUH PERSEPSI PROFESI GURU, LINGKUNGAN KELUARGA, EFIKASI DIRI TERHADAP MINAT MENJADI GURU - Wahyuni, Desti; Setiyani, Rediana (Economic Education Analysis Journal, 2017)
The purpose of this study is to describe the influence of perceptions about teachers profession, family environment, and self efficacy to interest being a teacher in student of education, both simultaneously and partially. The population in this study were student of Accounting Education Economic Faculty, Semarang State University force year 2014, amounting to 166 students. Technique of sampling uses population samples, so all of population becomes respondents of research. Methods of data collection using questionnaire. Data analysis method used is descriptive analysis and multiple linear regression analysis. The results showed that, simultaneously perceptions about teachers profession, family environment, and self efficacy affect to interest being a teacher by 52.1%, while the remaining 47.9% influenced by other variables out of models that not revealed in this study. Partially, perceptions about teachers profession are not proven to have an effect on the interest being a teacher by 0.34%. While the family environment and self efficacy have an effect on teacher's interest, respectively by 2.79%, and 38.07%